Exophytic Brainstem Cavernoma in the Floor of the Fourth Ventricle Midline Suboccipital Approach: 3-Dimensional Operative Video. Issue 3 (19th December 2018) - Bulstrode, Harry J C J; McMillen, Jason; Patel, Krunal; Correia, Jason; Guilfoyle, Matthew; Young, Adam; Santarius, Thomas; Kirollos, Ramez; Trivedi, Rikin
Abstract: This 3-dimensional operative video covers the suboccipital approach to a brainstem cavernoma of the floor of the fourth ventricle. Brainstem cavernomas are low-flow vascular lesions associated with a 2% to 6% annual bleed rate. Repeated bleeds typically result in progressive neurological deficit, and especially for exophytic lesions surgery may arrest this progression without significantly exacerbating pre-existing deficits. The approach to these lesions may be via any standard skull base approach, dictated in each lesion by the presentation to the pial surface. Here, we describe a suboccipital approach to an exophytic cavernoma of the floor of the fourth ventricle, arising caudal to the medial longitudinal fasciculus and facial colliculus. The 38-yr-old male patient had suffered a stepwise neurological deterioration secondary to repeated bleeds, and complete resection of the cavernoma demonstrated here arrested this progression. The patient has provided signed consent to video acquisition and storage at operation, and to publication of this material.